Exploring the multiple biotechnological potential of halophilic microorganisms isolated from two Argentinean salterns - Nercessian, Debora (2015)
The biodiversity and biotechnological potential of microbes from central Argentinean halophilic environments have been poorly explored. Salitral Negro and Colorada Grande salterns are neutral hypersaline basins exploded for NaCl extraction. As part of an ecological analysis of these environments, two bacterial and seven archaeal representatives were isolated, identified and examined for their biotechnological potential. The presence of hydrolases (proteases, amylases, lipases, cellulases and nucleases) and bioactive molecules (surfactants and antimicrobial compounds) was screened. While all the isolates exhibited at least one of the tested activities or biocompounds, the species belonging to Haloarcula genus were the most active, also producing antimicrobial compounds against their counterparts. In general, the biosurfactants were more effective against olive oil and aromatic compounds than detergents (SDS or Triton X-100). Our results demonstrate the broad spectrum of activities with biotechnological potential exhibited by the microorganisms inhabiting the Argentinean salterns and reinforce the importance of screening pristine extreme environments to discover interesting/novel bioactive molecules.